Encapsulation of probiotics for increased thermal stability for storage and increased viability passing through the gastro-intestinal tract - Li, Aaron Zongwei (Nanyang Technological University, 2020)
Probiotics are defined as living bacteria that, when administered in adequate amounts, confer a health benefit on the host. (Hill, Guarner, Reid, Gibson, & Merenstein, 2014) Therefore, more and more people are beginning to explore the use of probiotics supplements for their proposed health benefits. However, probiotics being living bacteria, are susceptible to temperature and environmental fluctuations. In order to be able to provide a certain health benefit to the host, these live bacteria should maintain a high enough level of viability throughout the food processing procedures, during the storage duration and while passing through the gastrointestinal tract. (Chávarri, Marañón, & Villarán, 2012) One of the most common food processing methods for inactivation of harmful pathogens is through the use of heat. At present, there are few probiotics that are stable at high temperatures, thereby increasing the urgency to improve their heat resistance either through identification of new heat-stable strains or to develop novel delivery systems to protect them. (Solanki et al., 2013) Hence, much interest has been gathered on using encapsulation as a means of delivery and protection of the probiotics to able survive the food processing procedures and eventually be viable in the gastrointestinal tract. In this study, the use of Maillard conjugation of whey protein with citrus pectin as encapsulants is explored for the encapsulation of Lactobacillus plantarum (DSM 12028) for increased thermal stability for storage and increased viability passing through the Gastrointestinal Tract. Viability of L.Plantarum encapsulated in 2% whey protein and 1% pectin (WP1) in room temperature (25°C) storage after 60 days was found to be 7 log units higher than free L.Plantarum cells. The encapsulation of WP1 also resulted in an increase in viability through the upper gastrointestinal tract with a log (CFU/g) of 8.15 compared to 4.90 in free unencapsulated L.Plantarum cells. WP1 also showed a high heat tolerance in pasteurization with only a 0.33 log units reduction after 30 minutes at 85°C.